AN INVESTIGATION ON PARTICLE SWARM OPTIMIZATION ALGORITHM FOR DISTRIBUTION SYSTEM PLANNING WITH DISTRIBUTED GENERATION - Shamshiri, Meysam; Gan, Chin Kim; Hasan, I. J.; Ab Ghani, Mohd Ruddin (2012)
Nowadays, technology advancement, the drive to reduce environmental pollution and power system restructuring have caused the increase in the utilization of Distributed Generations (DGs). One of the important aspects of the power system is the optimal operation of distribution networks. Therefore, the main objective of this paper is to investigate and to find the best solution for optimal operation of distribution networks which takes into account the impact of DG. Since optimal operation of distribution networks is an optimization problem with discrete and continuous variables, so it can be introduced as an integer problem that can be formulated by metaheuristic. In this regards, this paper presents the Particle Swarm Optimization (PSO) algorithm to solve the distribution planning problem with DG. In addition, case study on IEEE 34 buses system have been carried out to demonstrate the effectiveness of the PSO algorithm. And finally the performance of PSO algorithm is compared with Genetic Algorithm (GA).